Does brand orientation help B2B SMEs in gaining business growth?. Issue 4 (3rd May 2016) - Hirvonen, Saku; Laukkanen, Tommi; Salo, Jari
Abstract : Purpose: The purpose of this study is to examine the relationship between brand orientation and business growth in business-to-business (B2B) small- and medium-sized enterprises (SMEs). The authors also explore whether this relationship is moderated by internal firm-related factors (firm age, firm size) and/or external market-related factors (market life cycle, industry type). Design/methodology/approach: The authors develop and empirically test a conceptual model using data from 396 B2B SMEs operating in Finland. Structural equation modeling is used for testing the research hypotheses. Findings: Brand orientation contributes to business growth via two indirect paths, the first one going through brand performance and the second one going through brand performance and customer relationship performance. However, although the effects are positive, the results reveal that the regression coefficients are relatively small, implying only a limited impact of brand orientation on growth among B2B SMEs. The results further suggest that firm age, firm size and industry type moderate the brand performance–business growth relationship, whereas market life cycle moderates the effect of brand orientation on brand performance. Research limitations/implications: Future research could extend this study by examining brand orientation in industrial markets simultaneously with alternative strategic orientations, such as market, technology and innovation orientation. New moderator variables should also be considered, such as market or technological turbulence. Furthermore, given that this study uses a cross-sectional data set, it is recommended that future research should attempt to test the model using longitudinal data sets. Practical implications: B2B SMEs are able to gain business growth through developing a strong brand. However, brand orientation per se appears to be of limited relevance for such an endeavor. Consequently, managers of small industrial firms should consider brand orientation only with, and in comparison to, alternative strategic orientations. Originality/value: Brand orientation has been very rarely examined from the perspective of B2B firms or that of SMEs. Interestingly, the findings indicate that the performance benefits of brand orientation seem to be smaller among B2B SMEs than what earlier research would imply. The analysis of moderation effects offers additional insights into whether there are differences between industrial SMEs as to the relevance of brand orientation.